Revisiting Wujudiyyah and the Politics of Religious Orthodoxy in the Seventeenth-Century Aceh Sultanate - Sangidu; Eva Farhah; Imam Wicaksono; Shawy Shawy Ahmed Abdurrahem (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study examines the theological polemic between Wujudiyyah and the orthodox interpretations of Nuruddin ar-Raniri in the seventeenth-century Aceh Sultanate, which extended beyond differences in Sufi doctrine to exert direct influence on political power through takfīr edicts, book burnings, and executions. The novelty of this research lies in its integrative approach, employing Ibn ʿArabī’s theory of ontological pluralism to elucidate the dialectic between spiritual diversity and theological exclusion. The research adopts a qualitative-historical case study design, drawing on primary sources such as the Sufi manuscripts of Hamzah Fansuri and Syamsuddin al-Sumatrani, as well as the legal texts of Nuruddin ar-Raniri. Data were collected through document analysis, critical manuscript verification, and historiographical triangulation. The analysis was conducted using thematic classification grounded in the concepts of the transimmanence of the real and the unity of being. The findings demonstrate that the conceptual distinction between wahdat al-wujūd and wahdat al-shuhūd shaped the epistemological legitimacy of religious authority, while takfīr rulings and executions functioned as politico-religious instruments. The principal contribution of this study is the formulation of a contextual ontological pluralism that extends Ibn ʿArabī’s theoretical framework, while also revealing how texts, edicts, and repressive practices operated as hegemonic tools in the enforcement of orthodoxy. Its broader implication underscores the significance of Islam Nusantara studies as a model for understanding the dialectics of Sufism, orthodoxy, and political power, offering valuable insights into contemporary religion–politics relations.